1999
DOI: 10.1007/s002329900511
|View full text |Cite
|
Sign up to set email alerts
|

Ion Selectivity of the Cytoplasmic Binding Sites of the Na,K-ATPase: I. Sodium Binding is Associated with a Conformational Rearrangement

Abstract: Abstract. To investigate Na+ binding to the ion-binding sites presented on the cytoplasmic side of the Na,KATPase, equilibrium Na + -titration experiments were performed using two fluorescent dyes, RH421 1 and FITC, to detect protein-specific actions. Fluorescence changes upon addition of Na + in the presence of various Mg 2+ concentrations were similar and could be fitted with a Hill function. The half-saturating concentrations and Hill coefficients determined were almost identical. As RH421 responds to bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(84 citation statements)
references
References 36 publications
6
78
0
Order By: Relevance
“…Since only Na + ions bind electrogenically in the E 1 conformation of the ion pump [12,30], all ions other than Na + should have only a marginal effect on the fluorescence intensity (⌬F max /F 0 < 3%). In the following it will be shown that this is true for all other monovalent cations, however, some di-and trivalent cations are able to affect the fluorescence intensity of the styryl dye.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Since only Na + ions bind electrogenically in the E 1 conformation of the ion pump [12,30], all ions other than Na + should have only a marginal effect on the fluorescence intensity (⌬F max /F 0 < 3%). In the following it will be shown that this is true for all other monovalent cations, however, some di-and trivalent cations are able to affect the fluorescence intensity of the styryl dye.…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescence measurements were carried out in a Perkin-Elmer LS 50B fluorescence spectrophotometer as described in the recently published part I of this paper [30]. The excitation wavelength was set to 580 nm and the emission wavelength to 650 nm (slit width 15 nm and 20 nm, respectively).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations